Relation between macroeconomic variables and ASEAN stock index / Farah Amira Mohamed Nasser, Che Mohamad Asyraf Che Rosid and Nurul Syuhada Baharuddin - Mohamed Nasser, Farah Amira; Che Rosid, Che Mohamad Asyraf; Baharuddin, Nurul Syuhada (2017)
The changes in macroeconomic variables can give an effect to the fluctuation in securities trade. This phenomenon will surely give impact to the stock market index and will resulting in more trading occurred in the stock exchange market. Therefore, this study investigates the impact of macroeconomics variables to the stock index for ASEAN countries. The relationships between stock index and several macroeconomics variables are analyzed for five ASEAN countries including Malaysia, Singapore, Indonesia, Philippines and Thailand. Five macroeconomics variables which are gross domestic product, interest rate, inflation rate, exchange rate and unemployment rate are used to explain the variation of the stock index. Using yearly data and generalized least squares regressions, the results show strong significant relationships of all the macroeconomic variables to the stock index.